A Hermeneutics of Love for Community-Based, Participatory Action Research. (May 2016) - McInerney, Robert Garfield
This article presents a broad humanistic-existential framework in support of community-orientated, participatory action research. Beginning with Pink Floyd's The Wall as a pedagogic illustration of the aporia of community, three dispositions are offered for the community researcher: communitas, allopathy, and munificence. Each disposition is shown to be supported by particular shared burdens (hospitality, alterity, finitude, and supplementarity) within existence. From this theoretical framework, a model is provided for what is designated as a hermeneutics of love as a research practice in communities.